THE GENDER FACTOR IN THE DEMOGRAPHIC DEVELOPMENT OF SOCIETY - Mirzakhmedov, Abdurashid; Pardaeva, Sevara (Oriental Journal of History, Politics and Law, 2025)
One of the problems associated with the demographic quality of the population at a new stage of development of society is transsexualism among young people, that is, rejection of their own sexual status and transition to the status of the opposite sex. Psychological dissatisfaction of the population with their sexual status is expressed in the desire to see a person of their own sex in a person, as well as in the maximum "transfer" of their appearance to a woman. Therefore, the purpose of the article is a socio-philosophical analysis of the problems of violation of human sexual identity. In the article, the authors sought to make scientific conclusions based on a comparative analysis of foreign and domestic sociological studies.